War and peace [videorecording (DVD)] - Bondarchuk, Sergeĭ, 1920-1994; Savelʹeva, Li͡udmila, 1942-; Tikhonov, Vi͡acheslav, 1928-2009; Tolstoy, Leo, graf, 1828-1910 (Kultur, 2000)
A painstakingly detailed adaptation of the Tolstoy novel which follows the interconnected lives of a group of Russian aristocrats from 1805 to 1812, including Napoleon's invasion of Russia.